Dari Teks Menuju Konteks: Semiotika Dharmagita dalam Transformasi Masyarakat Modern - Ida Bagus Gde Yudha Triguna; Anak Agung Inten Mayuni (Jurnal Penelitian Agama Hindu, 2022)
The tradition of reading, singing, and interpreting religious literary texts gave birth to a didactic method called dharmagita. However, the implementation of the dharmagita tends to prioritize the aesthetic dimension, rather than the didactic dimension, so that it has the potential to hinder the transformation of religious texts in the context of religiosity. This article aims to reveal the semiotics of dharmagita as a strategic transformation of religious texts in the context of modern society. The study was conducted using a qualitative method based on a sociology of literature approach. The results of the study show that modernization affects traditional values ​​so that adaptation strategies are needed so that people are able to follow changes without losing moral and spiritual control. Dharmagita has a transformative role to enlighten society with values ​​in religious texts that are relevant to modern culture. In this context, improving the semiotic skills of dharmagita activists has an important role to optimize their ability to understand, interpret, and contextualize religious literary texts in actual-practical life.